Peran Guru Sebagai Garda Utama Penerapan Pendidikan Anti Korupsi Di Lingkungan Sekolah - Risnu Puja Kesuma; Anggun Sakinah; Zein Norika Marsyanda (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study highlights the strategic role of teachers in integrating anti-corruption values into the world of education. Teachers not only function as transmitters of teaching materials, but also as agents of character formation who instill the values of honesty, responsibility, and integrity. Through a curriculum integrated with anti-corruption values, inspiring learning methods, and a conducive learning environment, teachers have an important role in fostering anti-corruption awareness from an early age. Teachers' exemplary behavior in everyday life and involvement in non-formal activities also strengthen the formation of students' character. Collaboration between schools, families, and communities is a supporting factor in creating a young generation with high integrity. Thus, teachers are at the forefront of efforts to build a nation free from corruption.